The roots of environmental consciousness : popular tradition and personal experience - Hussey, Stephen, 1967-; Thompson, Paul, 1935- (Routledge studies in memory and narrative, 2000)
This book examines the roots of contemporary environmental consciousness and action in terms of both popular experience and tradition. A wide range of case-studies explore traditions and myths that shape our environmental thought.